1973
DOI: 10.1172/jci107503
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Lymphocyte Cell Surface Markers during the Course of Systemic Lupus Erythematosus

Abstract: A B S TRA CT Peripheral blood lymphocytes from 23 patients with active systemic lupus erythematosus (SLE) were serially studied. Changes in bone marrow-derived lymphocytes (B cells), as measured by surface Ig receptors and C3 receptors, and in thymus-derived cells (T cells) measured by rabbit T-cell-specific antiserum and E-binding techniques, were correlated with fluctuations in clinical disease activity and treatment. In normal controls B-and T-cell percentages remained relatively stable, although the situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0

Year Published

1975
1975
1980
1980

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(55 citation statements)
references
References 35 publications
5
50
0
Order By: Relevance
“…The authors and others (23)(24)(25) have found some indications of the clinical correlations that motivated this work. The study of a large group of untreated S L E patients has shown that the populations of lymphocytes that bear receptors for sheep red blood cells, as well a s those bearing receptors for the Fc fragment of IgG, are markedly diminished in SLE patients (6).…”
Section: Discussionmentioning
confidence: 85%
“…The authors and others (23)(24)(25) have found some indications of the clinical correlations that motivated this work. The study of a large group of untreated S L E patients has shown that the populations of lymphocytes that bear receptors for sheep red blood cells, as well a s those bearing receptors for the Fc fragment of IgG, are markedly diminished in SLE patients (6).…”
Section: Discussionmentioning
confidence: 85%
“…I t is therefore possible that alterations in lymphocyte membranes or even virally coded membrane antigens are responsible for producing antibodies that cross-react with similar determinants in a heterogeneous panel of normal test lymphocytes. N o evidence for specific lupusrelated antigens has yet been produced, despite repeated attempts to demonstrate such specificity (6,7,9,41). A recent report by Lewis et a1 (42) might be interpreted as evidence for possible viral antigens detectable in peripheral blood lymphoid cells of patients with active SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescein isothiocyanate (FITC) conjugated goat antiserum to h u m a n IgG, IgA, and IgM was obtained f r o m Hyland Laboratories (FITC-Anti-Ig). Monospecific rabbit anti-IgG, IgA, and IgM sera were prepared on immunoabsorbent columns and labeled with FITC as previously described (1).…”
Section: Methodsmentioning
confidence: 99%
“…is increased (1)(2)(3). T h e percent of cells bearing a second B-lymphocyte marker, the receptor for the third component of complement, is decreased (1).…”
mentioning
confidence: 99%